2017
DOI: 10.1038/s41598-017-14948-y
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Dirac points and high spin polarization in ferromagnetic-strain graphene superlattices

Abstract: Spin-dependent energy bands and transport properties of ferromagnetic-strain graphene superlattices are studied. The high spin polarization appears at the Dirac points due to the presence of spin-dependent Dirac points in the energy band structure. A gap can be induced in the vicinity of Dirac points by strain and the width of the gap is enlarged with increasing strain strength, which is beneficial for enhancing spin polarization. Moreover, a full spin polarization can be achieved at large strain strength. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It should be pointed out that the negative shift is associated with the Klein tunneling effect. [35][36][37][38] In order to explore the effect of combined modulation, the calculated results for GHL shift are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out that the negative shift is associated with the Klein tunneling effect. [35][36][37][38] In order to explore the effect of combined modulation, the calculated results for GHL shift are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…As in the case of semiconductor superlattices, most of the works in graphene superlattices are devoted to the study of single-period structures. In fact, there are extensive studies in electrostatic 17 20 , 20 23 , magnetic 24 29 , and strain 30 34 graphene superlattices. Regarding biperiodic superlattices in graphene the few works found in the literature address aspects related to the electron transport, band structure, and resonant peak splitting 35 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was shown experimentally that graphene can sustain strain up to 25% [19]. In recent years, the electronic, spintronic and valleytronic properties of strained graphene structure have gained much attention [20][21][22][23][24][25][26][27][28][29]. Cao et al [22] showed that when the armchair direction uniaxial strain is applied to a graphene junction, the transmission probability symmetry breaks with respect to the angle of incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [22] showed that when the armchair direction uniaxial strain is applied to a graphene junction, the transmission probability symmetry breaks with respect to the angle of incidence. Spin-dependent transport properties of graphene superlattices under strain were investigated by Wu et al [23]. They demonstrated that high spin polarization can be achieved in such a system due to the presence of strain.…”
Section: Introductionmentioning
confidence: 99%